Penegakan Hukum Pidana Terhadap Korban Pecandu Narkoba Di Indonesia - Amrizal Siagian (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2015)
Abstract:The government's criminal policy on the issuance of a drug-related law No. 35 of 2009, especially for drug addicts, needs to be implemented in accordance with the mandate of the constitution. That the government has an obligation to protect the homeland and its citizens from any kind of threat. Including the threat of the dangers of drugs, which are consciously and deliberately spread to the community, especially the younger generation as the nation's successor. Currently, drug users are estimated to reach 5.1 million, or even more. Because the number of drug users is like an iceberg (ice berg) and experiences a dark number (dark number). It is highly hoped that the criminal policy on the issuance of the law will be able to overcome or at least reduce the number of drug users, one of which is creating a new breakthrough by decriminalizing drug users without having to get imprisonment. As stated that the legal protection guarantee provided for narcotics addicts is regulated through Law No. 35 of 2009 concerning Narcotics by providing both medical and social rehabilitation as stated in Article 54 of the Narcotics Law. Namely that